2007
DOI: 10.1007/s11892-007-0036-0
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidemia in type 2 diabetes mellitus

Abstract: Cardiovascular disease is a significant cause of morbidity and mortality in patients with diabetes mellitus (DM). DM is now recognized as a risk equivalent for coronary heart disease. The lipid profile in patients with type 2 DM is characterized by elevated triglycerides, low levels of high-density lipoprotein cholesterol, and small dense low-density lipoprotein cholesterol (LDLC) particles and is believed to be a key factor promoting atherosclerosis in these patients. Both primary and secondary prevention stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 39 publications
2
49
0
1
Order By: Relevance
“…The elevation of cholesterol in diabetic subjects is attributed to increased availability of acetyl coenzyme-A, the starting substrate for cholesterol synthesis in human beings, due to increased fatty acid utilization as well as fatty acid oxidation for energy purposes because of non-availability of glucose due to either deficiency of insulin or due to sub-normal functioning of insulin (1). The increased level of cholesterol in diabetic subjects may cause micro or macro vascular changes leading to an array of diabetic cardio-vascular complications (22)(23)(24)(25)(26) .The observed raise in plasma cholesterol in diabetic subjects (group-1 & group-2) as compared to normal subjects (p<0.001) as evident from the table-2 is in agreement with the earlier reports (27)(28)(29). It has been observed by many workers that the erythrocyte membrane cholesterol is elevated in diabetic population (13,30).…”
Section: Discussionsupporting
confidence: 89%
“…The elevation of cholesterol in diabetic subjects is attributed to increased availability of acetyl coenzyme-A, the starting substrate for cholesterol synthesis in human beings, due to increased fatty acid utilization as well as fatty acid oxidation for energy purposes because of non-availability of glucose due to either deficiency of insulin or due to sub-normal functioning of insulin (1). The increased level of cholesterol in diabetic subjects may cause micro or macro vascular changes leading to an array of diabetic cardio-vascular complications (22)(23)(24)(25)(26) .The observed raise in plasma cholesterol in diabetic subjects (group-1 & group-2) as compared to normal subjects (p<0.001) as evident from the table-2 is in agreement with the earlier reports (27)(28)(29). It has been observed by many workers that the erythrocyte membrane cholesterol is elevated in diabetic population (13,30).…”
Section: Discussionsupporting
confidence: 89%
“…Previous reports from epidemiological and clinical studies have revealed that factors other than hyperglycemia are also important contributors in patients with diabetes, such as abnormalities in lipid and protein metabolism [4,5]. Abnormalities in lipid metabolism are also seen in diabetic patients [6], nevertheless pharmacological investigations are needed in severe cases of hyperglycemia and hyperlipidemia [7].…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative changes consists of increase of triglyceride (TG), LDL-C and HDL-C, non-enzymatic glycation of LDL and non-enzymatic glycation of high density lipoprotein (HDL) [4]. Due to the abnormalities in lipoproteins, diabetes mellitus is associated with cardiovascular and cerebrovascular morbidity and mortality worldwide [5]. Dyslipidemia affects approximately 70% to 97% of people with diabetes [6].…”
Section: Introductionmentioning
confidence: 99%